Integration of LED/SC chips (matrix) in reverse mode with solar energy storage - Osinsky, V.I.; Masol, I.V.; Feldman, I.Kh.; Diagilev, A.V.; Sukhovii, N.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
In this work, for the first time we investigated controlling the quantum efficiencies of III-nitride LED/SC (solar cells) new energy accumulating elements and supercapacitors as energy storage devices (Enestors). It has been shown that the atomic content in these microenergetic devices gives large possibilities for energy storage from solar light. The developed technique is promising to make ideal new functional LED, LD and SC with a high quantum efficiency and small leakage. This technology can be realized using Si/A³B⁵ integrated processor technology epitaxy with computer driving.